Effectiveness Development Learning Practices Laboratory Prodi DIII Radiodiagnostic And Radiotherapy Technic Purwokerto - Rini Indrati; Sugiyanto Sugiyanto; Dartini Dartini (Jurnal LINK, 2013)
A study to determine the effectiveness of the Laboratory Practice Learning Development Prodi D-III Techniques Radiodiagnostic And Radiotherapy Purwokerto.  This type of research is descriptive quantitative study approach. The design of the study is a survey designed to capture engineering data using questionnaires and study documentation. A total of 70 Clinical Instructors involved in the study, and as many as 98 students will see the achievements of PKL value I. Data were analyzed using descriptive with standard Effectiveness. Research results showed that the Learning Development Laboratory Practices conducted by Prodi D-III Technique Radiodiagnostic and Radiotherapy Purwokerto assessed effectively with value effectiveness Old Time Orientation 90,00%, Communication Ability perform 88,57%, perform administrative ability 85,71%, the ability of Patient Preparation of 88,57%, the ability to do Preparation Equipment 87,14%, Patient Setting capabilities 91,43%, the ability Organize X Ray 90,00%, Radiation Protection Capability Set 84,29%, the ability to conduct evaluation of radiographs 82,86%, Performance 100,00%, Score Competency Exam 100,00%, Case Reports 100,00%, and the score comprehensive exam PKL 100,00%.